PEMBINAAN TERPIDANA HUKUMAN MATI DI LAPAS PEREMPUAN - M. Daffa Baqir Ashidiqy; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Indonesia implements death penalty. This study raises issues including the legal basis and form of death penalty itself. This study aims to answer the problems described. The type of research adopted uses normative law and a qualitative approach. Based on the results of the study, there are differences in the legal consequences of the term death row convicts and the convicts themselves. So it can be concluded that these regulations need to be harmonized in order to provide effectiveness to both parties by Correctional Institutions (LAPAS). Implementation of coaching activities by LAPAS related to Death Convicts or Convicts to prioritize the types and aspects of criminal acts as a support for the effectiveness of achieving punishment